Colorado naturalist wins religion prize - Guardian UK - U.S. Associated Press sources, author; Guardian Unlimited; Guardian Newspapers Limited, publisher (Colorado State University. Libraries, 2003)
A pioneer in environmental ethics who says humanity has treated nature "disgracefully'' was named Wednesday as this year's recipient of a religion prize that is billed as the world's richest annual award.

The Rev. Holmes Rolston III was awarded the Templeton Prize for Progress in Religion. The prize is 725,000 British pounds, roughly $1.2 million. Rolston said at a news conference that he would use all the prize money to endow a chair in religion and science at his alma mater, Davidson College in North Carolina.

"I've spent my life in a lover's quarrel with the two disciplines I love: science and religion,'' Rolston said. "I had to fight - or maybe better, challenge - both theology and science to love nature.''
Keywords: Rolston, Holmes, 1932-2025